2021
DOI: 10.1111/ajd.13677
|View full text |Cite
|
Sign up to set email alerts
|

An Australian tertiary hospital analysis of outpatient dermatology clinical and demographic characteristics

Abstract: Objectives Literature on dermatology outpatient demographic and clinical data is limited, and the few studies on this topic are mainly conducted overseas, with medical systems and case mix different to Australia. This study presents demographic data relating to dermatology public outpatient referrals to a tertiary hospital in Brisbane, Australia, and determines what additional structured data should be collected to formulate and evaluate initiatives to address service issues such as referral quality, triage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Furthermore, most category 3 patients in 2020 (57.1%) and 2021 (61.3%) were also seen in time, marking an improvement from the earlier years of the study period. This is compared to the tertiary hospital in Brisbane which found that only the majority of category 3 patients (60%) were seen within the expected timeframe (365 days) during its 4‐year study period 9 . While it is commendable that the majority of category 1 and 3 patients were seen in time during 2020 and 2021 at the Cairns Hospital, further strategies should be considered to address the wait times that patients, particularly category 2 patients, experience.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, most category 3 patients in 2020 (57.1%) and 2021 (61.3%) were also seen in time, marking an improvement from the earlier years of the study period. This is compared to the tertiary hospital in Brisbane which found that only the majority of category 3 patients (60%) were seen within the expected timeframe (365 days) during its 4‐year study period 9 . While it is commendable that the majority of category 1 and 3 patients were seen in time during 2020 and 2021 at the Cairns Hospital, further strategies should be considered to address the wait times that patients, particularly category 2 patients, experience.…”
Section: Discussionmentioning
confidence: 95%
“…One study, which analysed the dermatology outpatient demographics at a metropolitan tertiary hospital in Brisbane, Queensland, found that during the 4-year period between January 2016 and December 2019, 7140 new patients were referred. 9 Similarly, another study that analysed the dermatological services offered at a rural tertiary hospital in the Northern Territory, determined that 330 new appointments were scheduled in a 1-year period in 2016. 10 Given that Cairns Hospital is a regional non-tertiary hospital and that the population within its catchments is projected to continually grow, its level of resourcing should be reviewed so that it is able to meet this demand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the average time to specialist advice reported in the studies utilising a SAFT service was faster compared to the average time required for patients referred to a large public dermatology clinic to be seen face-to-face. 54 Only a small proportion of SAFT patients were recommended a subsequent face-to-face appointment thereby allowing more patients to be adequately managed in primary practice ultimately reducing the burden of the dermatology outpatient setting and preventing patients the need to travel to metropolitan centres for care. Furthermore, triaging dermatological patients, and determining which patients need subsequent face-to-face review, could increase efficiency of health-care systems.…”
Section: Waiting Times and Face-to-face Appointmentsmentioning
confidence: 99%